2003
DOI: 10.1897/02-420
|View full text |Cite
|
Sign up to set email alerts
|

Formation of benzo[a]pyrene and 7,12‐dimethylbenz[a]anthracene adducts in vascular endothelia of cytochrome P4501A–induced chicken embryos

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread in the environment and birds may be exposed to PAHs via diet, from preening feathers contaminated with oil, or through contamination of the eggshell during embryo development. In the present study, tissue distribution and the cell-specific binding of two labeled PAHs, benzo[a]pyrene ([3H]BaP) and 7,12-dimethylbenz[a]anthracene ([3H]DMBA), were examined in chicken embryos exposed in ovo to CYP1A inducers. Tape-section autoradiograms revealed high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…The most common DMBA-induced mutations in control diet rats were A:T?T:A transversions (42%), followed by G:C?T:A transversions (19%), which are consistent with the abundance of DMBA-dA and DMBAdG adducts observed in the mammary gland, a target tissue for DMBA carcinogenicity in the rat . Although DMBA-induced DNA adducts in the heart were neither measured nor characterized in the present study, DNA-adduct formation has been reported in the heart and vascular endothelia of rodents and birds exposed to DMBA [Wang and Su, 2001;Granberg et al, 2003]. These results and ours suggest that DMBA forms adducts in the heart that lead to gene mutations.…”
Section: Discussioncontrasting
confidence: 57%
“…The most common DMBA-induced mutations in control diet rats were A:T?T:A transversions (42%), followed by G:C?T:A transversions (19%), which are consistent with the abundance of DMBA-dA and DMBAdG adducts observed in the mammary gland, a target tissue for DMBA carcinogenicity in the rat . Although DMBA-induced DNA adducts in the heart were neither measured nor characterized in the present study, DNA-adduct formation has been reported in the heart and vascular endothelia of rodents and birds exposed to DMBA [Wang and Su, 2001;Granberg et al, 2003]. These results and ours suggest that DMBA forms adducts in the heart that lead to gene mutations.…”
Section: Discussioncontrasting
confidence: 57%
“…Treatment of mice with benzo(a)pyrene (B[a]P) or dimethylbenzanthracene induces bioactivation of drug-metabolizing enzymes and irreversible binding of hydrocarbon metabolites to endothelial cells (EC). These data suggest that PAHs may augment atherosclerosis by a process that involves EC damage (Granberg et al 2003), possibly via apoptosis. The importance of apoptotic cell death to the atherosclerotic process is well documented (Dimmeler et al 1998; Geng and Libby 1995; Isner et al 1995).…”
Section: Introductionmentioning
confidence: 88%
“…In ovo studies showed that the bile, liver, kidneys, heart, and leptomeninges were the most contaminated organs of chicken embryos exposed to PAHs; in part, the bioactivity of the PAHs in these tissues was facilitated by the formation of PAH adducts in blood vessel endothelium. 133 In chickens hatched from the PCB-126 exposed eggs, expression levels of Cyp1a4 mRNA in whole liver tissue increased 29-fold. 134 Damage to hepatic membrane structure and function was correlated with the increased mortality in chicken embryos exposed to PCB-126.…”
Section: Adverse Effects Of Dioxins In Fish Birds and Other Wildlifementioning
confidence: 99%